2016
DOI: 10.1021/acs.molpharmaceut.6b00870
|View full text |Cite
|
Sign up to set email alerts
|

CD44 Receptor Targeting and Endosomal pH-Sensitive Dual Functional Hyaluronic Acid Micelles for Intracellular Paclitaxel Delivery

Abstract: A novel CD44 receptor targeting and endosome pH-sensitive dual functional hyaluronic acid-deoxycholic acid-histidine (HA-DOCA-His) micellar system was designed for intracellular paclitaxel (PTX) delivery. The HA-DOCA-His micelles exhibited desirable endosome pH (5.0-6.0)-induced aggregation and deformation behavior verified by size distribution, critical micellar concentration, and zeta potential changes. The HA-DOCA-His micelles presented excellent encapsulation efficiency and loading capacity of 90.0% and 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…Hyaluronic acid (HA) is a macromolecule from a natural source, widely used in biomedical applications due to its good biocompatibility, biodegradability, and low toxicity, especially in cosmetics, treatments for arthritis, and drug delivery [ 19 , 20 , 21 , 22 , 23 , 24 ]. Recent studies have demonstrated that the surface of cancer cells over-express the CD44 receptors on their surface, to which HA strongly binds [ 25 , 26 , 27 , 28 , 29 , 30 ]. Therefore, HA can be utilized as a target ligand for tumor-targeted drug delivery [ 31 , 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hyaluronic acid (HA) is a macromolecule from a natural source, widely used in biomedical applications due to its good biocompatibility, biodegradability, and low toxicity, especially in cosmetics, treatments for arthritis, and drug delivery [ 19 , 20 , 21 , 22 , 23 , 24 ]. Recent studies have demonstrated that the surface of cancer cells over-express the CD44 receptors on their surface, to which HA strongly binds [ 25 , 26 , 27 , 28 , 29 , 30 ]. Therefore, HA can be utilized as a target ligand for tumor-targeted drug delivery [ 31 , 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accompanied by PTX preloading, the NPs induced strong tumor apoptosis, cellular arrest, and cytotoxic activity (Ravar et al, 2016;Su et al, 2018;Zhao et al, 2018). After activation by the TME (pH, redox), HA-NPs exhibited great lysosomal release and antitumor efficacy (Yin et al, 2015;Liu et al, 2016Liu et al, , 2020Zhong et al, 2016;Han et al, 2019).…”
Section: Hyaluronic Acid (Ha) and Chondroitin Sulfate (Cs)mentioning
confidence: 99%
“…Similar systems based on GAG/DOCA were developed in recent years: ChS‐DOCA nanoparticles for DOX delivery (J.‐Y. Lee, Chung, Cho, & Kim, ), HA‐DOCA‐histidine micelles for intracellular paclitaxel (PTX) delivery (Yanhua Liu, Zhou, Wang, et al, ), phenylboronic acid‐decorated ChS‐DOCA system for DOX delivery (J. Y. Lee, Chung, Cho, & Kim, ), ChS‐DOCA/DOX nanoparticle for the therapy of CD44 receptor‐expressing ovarian cancers (J.‐Y. Lee et al, ), ChS‐DOCA conjugates for docetaxel delivery (M. Liu, Du, & Zhai, ).…”
Section: Polysaccharidesmentioning
confidence: 99%